EFFECT of Ananas comosus crown and Punica granatum peel mixture to inhibit post-harvest Mangifera indica fungal (Aspergillus niger) - Mohamad, Sarina; Farhana Adilah Roslan, Nur; Sarina Sulaiman, Siti; Syafiqah Rahim, Nur; Mohd Firdaus Azis, Tun; Zuraina Mohd Yusof, Farida (International Journal of Engineering and Technology, 2018)
Aspergillus niger is a predominant fungus that grow on post-harvest mango (Mangifera indica) which lead to crops failure and quality reduction. Therefore, this study was carried out to utilize the fruit waste, Ananas comosus crown and Punica granatum peel to inhibit A. niger. The wastes were extracted by soxhlet extraction method. The antifungal activity of pineapple crown and pomegranate peel crude extracts was tested on A. niger using well diffusion method at different ratio; initial ratio (2:1, 1:1 and 1:2 respectively); and further ratio (4:6, 3:7, 2:8 and 1:9 respectively). The positive control (commercial fungicide) and negative control (100% acetone, methanol and sterile distilled water) were tested against A. niger. The findings revealed that the best further ratio, 2:8 (34.33±1.04 mm) posses better effectiveness to inhibit A. niger compared to the best initial ratio, 1:2 (30.17±0.76 mm) of pineapple crown to pomegranate peel respectively (p=0.01). While for positive controls, Brand X (34.17±1.04 mm) showed the highest effectiveness to inhibit A. niger and by comparing with 2:8 of pineapple crown to pomegranate peel ratio showed no significant value (p=0.85). Therefore, this study revealed that at the ratio 2:8 of pineapple crown to pomegranate peel mixture has a great potential to be formulated as commercial biofungicide by utilizing the fruit waste.